2022
DOI: 10.1371/journal.pone.0263718
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying rural disparity in healthcare utilization in the United States: Analysis of a large midwestern healthcare system

Abstract: Purpose The objective of this study is to identify how predisposing characteristics, enabling factors, and health needs are jointly and individually associated with epidemiological patterns of outpatient healthcare utilization for patients who already interact and engage with a large healthcare system. Methods We retrospectively analyzed electronic medical record data from 1,423,166 outpatient clinic visits from 474,674 patients in a large healthcare system from June 2018-March 2019. We evaluated patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 33 publications
(36 reference statements)
0
17
0
Order By: Relevance
“…Unfortunately, most available studies in either developed 1 - 6 , 11 , 12 , 15 or developing 7 - 10 , 13 , 14 countries have compared outcomes between rural and urban patients admitted to hospitals located at their own place of residence. Such investigations often compare the facilities, competencies, and accessibilities of hospitals rather than the risk factors between rural and urban individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, most available studies in either developed 1 - 6 , 11 , 12 , 15 or developing 7 - 10 , 13 , 14 countries have compared outcomes between rural and urban patients admitted to hospitals located at their own place of residence. Such investigations often compare the facilities, competencies, and accessibilities of hospitals rather than the risk factors between rural and urban individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Our study adds to the sparse literature on the challenges related to FCs’ preparedness to support physical activity in the post-discharge period and stakes out important new ground by charting this issue specifically in the rural context. Our findings are embedded in rural communities, which are typified by older age and higher levels of chronicity [ 10 ], but less access to the healthcare system that their urban counterparts [ 21 ]. Consequently, FCs play an outsized role in rural healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review and meta-analysis, post-discharge follow-up was also found to be effective in reducing hospital readmissions [ 35 ]. Follow-up for the FCs of patients at risk for hospital readmission in rural communities is particularly crucial because these communities have minimal formal supports in place and patients in these communities have worse health status and lower primary and specialty health care use than their urban counterparts [ 55 ].…”
Section: Discussionmentioning
confidence: 99%